The Influence of Economic Growth, Socio-Economics and Food Security on the Incidence of Stunting in Toddlers in Indonesia - Dwi Darma Puspita Sari; Rahma Nida; Hamira Hamira; Halia Butra Aini (Lembaga Teewan Journal Solutions, 2026)
This study aims to analyze the influence of economic growth, socio-economic factors (expected years of schooling and poverty), and food security on the incidence of stunting among toddlers across 34 provinces in Indonesia. A quantitative method was applied using panel data regression for the 2018-2024 period, with the Fixed Effect Model (FEM) selected as the most appropriate estimation approach. The results indicate that economic growth, expected years of schooling, poverty, and food security simultaneously have a highly significant effect on the fluctuation of regional stunting rates. Partially, expected years of schooling and food security exhibit a negative and highly significant impact on reducing the prevalence of stunting. Poverty increases the risk of stunting, though its direct impact is cushioned by government interventions, rendering it insignificant at the 5% level. Furthermore, macroeconomic growth does not significantly reduce stunting, reflecting the issue of non-inclusive growth. In conclusion, interventions focusing on improving socio-economic conditions and food security are highly necessary and more effective in alleviating stunting than relying solely on aggregate macroeconomic growth, highlighting the need for a more even distribution of economic development